Are people better at recognizing ambivalent sexism on the basis of the non-standard profiles than the standard ASI ones - Chisango, Tadios; Javangwe, Gwatirera (Springer Verlag, 2019)
Kilianski and Rudman (1998) developed “standard” profiles of a benevolent and a hostile sexist man from the Ambivalent Sexism Inventory (ASI) and tested if a U.S. sample of female students would perceive them as referring to the same person (i.e. an ambivalent sexist). Results showed that although they appraised the benevolent sexist profile favourably, and the hostile sexist one unfavourably, they considered it unlikely that they could refer to the same man. We developed “non-standard” profiles similar to those used by Kilianski and Rudman, with the major difference that they were not made directly from the ASI, but on the basis of attitudes and actions of a realistic soap-opera character, and tested if they would be considered as referring to the same individual by a sample of 238 undergraduate students (81 males and 157 females) at the University of Zimbabwe. Our results showed that both male and female participants found it as difficult to detect ambivalent sexism on the basis of non-standard ASI profiles as on the basis of standard ASI profiles.